New single nucleotide polymorphism G5508A in the SEPT12 gene may be associated with idiopathic male infertility in Iranian men - Maryam Shahhoseini; Mahnaz Azad; Marjan Sabbaghian; Mohammad Reza Akhoond; Reza Salman-Yazdi; Mohammad Ali Sadighi Gilani; Hamid Gourabi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Male infertility is a multifactorial disorder, which affects approximately 10% of couples at childbearing age with substantial clinical and social impact. Genetic factors are associated with the susceptibility to spermatogenic impairment in humans. Recently, SEPT12 is reported as a critical gene for spermatogenesis. This gene encodes a testis specific member of Septin proteins, a family of polymerizing GTP-binding proteins. SEPT12 in association with other Septins is an essential annulus component in mature sperm. So, it is hypothesized that genetic alterations of SEPT12 may be concerned in male infertility. Objective: The objective of this research is exploration of new single nucleotide polymorphism G5508A in the SEPT12 gene association with idiopathic male infertility in Iranian men. Materials and Methods: In this case control study, 67 infertile men and 100 normal controls were analyzed for genetic alterations in the active site coding region of SEPT12, using polymerase chain reaction sequencing technique. Fisher exact test was used for statistical analysis and p<0.05 was considered as statistically significant. Results: Genotype analysis indicated that G5508A polymorphic SEPT12 alleles were distributed in three peaks of frequency in both control and diseases groups. Categorization of the alleles into (GG), (GA), (AA) types revealed a significant difference between infertile patients (azoospermic and asthenospermic) and normal controls (p=0.005). Conclusion: According to our finding we suggest that G5508A polymorphism in SEPT12 gene can affect spermatogenesis in men, the opinion needs more investigation in different populations.